The Influence of Anodizing Electrolyte Concentration on Ni-P Deposition on Anodic Aluminum Oxide (AAO) - Rizkia, Vika; Susanto, Iwan; Belyamin; Garjati, Vina Nanda; Hapsari, Ade Utami; Raharjo, Jarot; Damisih; Pravitasari, Retna Deca (Jurnal Sains Materi Indonesia, 2025)
Aluminum alloys suffer from deficiencies in surface performance due to insufficient resistance to corrosion and mechanical qualities in harsh environments. Therefore, it is crucial to apply a protective surface modification during the manufacturing process of the aluminum component. The electroless deposited Ni-P shows great potential as a protective coating due to its simple manufacturing process and outstanding performance. This study investigates the effect of oxalic acid concentration in the anodizing process on electroless Ni-P coating. In this study, Anodic Aluminum Oxide (AAO) is formed by an anodizing process on 0.3,0.5, and 0.7 oxalic acids prior to Ni-P electroless deposition. The resulting Ni-P layer has a nodular-like morphology with a size in the order of 0.5 m or less. Moreover, the AAO surface is covered by a thin and tightly formed layer of nickel particles. The EDX analysis shows the oxygen percentage falls by up to 70% after Ni deposition in all anodizing parameters, as compared to the anodized specimens alone. In addition, the nickel content gradually decreases as the concentration of oxalic acid increases from 0.3 M to 0.7 M.